Food Anti-counterfeiting and Traceability Based on DNA Storage: Technology, Challenges and Prospects - SONG Yafeng, XING Ranran, LIANG Xiaoke, GONG Na, ZHEN Zixuan, ZHANG Jiukai, CHEN Ying (Shipin Kexue)
Food anti-counterfeiting and traceability are important ways to ensure food safety. In response to the upgrading of counterfeiting means, a variety of identification technologies have been gradually developed, which play a crucial role in the field of food quality and safety. In recent years, relying on the advantages of DNA molecules, more advanced and precise identification and tracking technologies have been developed, which provide new ideas for the establishment of an efficient anti-counterfeiting and accurate traceability system for food safety monitoring. This paper outlines the development process of DNA storage technology and DNA traceability code, describes the current status of and latest progress in the application of DNA traceability code in food anti-counterfeiting and traceability, and discusses the necessity of interdisciplinary cooperation in promoting the development of DNA traceability technology, as well as sustainability and safety issues that may be encountered in the implementation process. Finally, future trends in the development of DNA traceability technology are envisioned, and possible solutions are proposed for the current challenges, aiming to provide more scientific and efficient means for food authenticity identification and origin tracing.